Bio-gas production potential of ruminant and non-ruminant animal excreta (Indian Journal of Animal Production and Management, 2018)
This research work was carried out to evaluate the bio-gas production potential of four different substrates  viz. ruminant dung (cattle and goat) and non-ruminant excreta (pig and poultry). The bio-gas production  potential of non-ruminants excreta was found to be significantly higher than ruminant excreta due to less  fibre content, presence of undigested fermentable carbohydrates (volatile solids) and reduced nitrogen  content. The bio-gas production potential of pig excreta was found to be significantly (P
Keywords: Animal excreta; Bio-gas production potential; Non-ruminants; Ruminants